2020
DOI: 10.1158/0008-5472.can-19-2714
|View full text |Cite
|
Sign up to set email alerts
|

FGF Trapping Inhibits Multiple Myeloma Growth through c-Myc Degradation–Induced Mitochondrial Oxidative Stress

Abstract: Multiple myeloma, the second most common hematologic malignancy, frequently relapses because of chemotherapeutic resistance. Fibroblast growth factors (FGF) act as proangiogenic and mitogenic cytokines in multiple myeloma. Here, we demonstrate that the autocrine FGF/FGFR axis is essential for multiple myeloma cell survival and progression by protecting multiple myeloma cells from oxidative stress-induced apoptosis. In keeping with the hypothesis that the intracellular redox status can be a target for cancer th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 62 publications
5
33
0
Order By: Relevance
“…Multiple myeloma is the world's second most common hematologic malignancy with high heterogeneity (Ronca et al, 2020). Currently, various prognostic models have been established to guide risk stratification and predict patient survival (Kyrtsonis et al, 2009), but few of them were incorporated into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma is the world's second most common hematologic malignancy with high heterogeneity (Ronca et al, 2020). Currently, various prognostic models have been established to guide risk stratification and predict patient survival (Kyrtsonis et al, 2009), but few of them were incorporated into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from WM cell lines (BCWM.1; MWCL.1), as previously reported. 42,44,45 RNA samples were processed using WT PLUS Reagent Kit, according to manifacturer's protocol (Thermo Fisher Scientific, Waltham, MA, USA). Wide mRNA-transcriptome profiling was assessed using Clariom D Human array (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Transcriptome Profilingmentioning
confidence: 99%
“…In vivo studies were performed as previously reported. 30,42,45 A detailed description is provided within the Supplemental file.…”
Section: Transcriptome Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…In common with other pentraxins, the C -terminal portion of PTX3 includes the pentraxin-signature [ 17 ] whereas its unique N -terminal extension is responsible for binding to different members of the fibroblast growth factor (FGF) superfamily (including FGF2, FGF6, FGF8b, FGF10, and FGF17), thus preventing their interaction with all members of the FGFR family (FGFR1–4) [ 18 , 19 , 20 ]. Thus, PTX3 inhibits FGF-dependent responses, such as endothelial cell proliferation in vitro and angiogenesis in vivo [ 19 , 21 , 22 ], and exerts an oncosuppressive effect on FGF-dependent tumors, including multiple myeloma, melanoma, fibrosarcoma, lung, prostate, and bladder cancers [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In a therapeutic perspective, these findings led to the identification of the PTX3-derived small molecule NSC12 as the first orally available FGF trap able to inhibit the activity of all the members of the canonical FGF family by preventing their binding to FGFR1, 2, 3, and 4 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%